2021
DOI: 10.4102/safp.v63i1.5236
|View full text |Cite
|
Sign up to set email alerts
|

Transient gestational hypertension and pre-eclampsia: Two case reports and literature review on the need for stringent monitoring

Abstract: Transient gestation hypertension is a contributor to adverse pregnancy outcomes particularly when it progresses to pre-eclampsia (PE). This requires frequent monitoring. We illustrate the need for stringent monitoring of gestational hypertension, transient gestational hypertension (TGH) and PE without severe features and conducted a brief rapid review of the literature. Two cases are presented: Firstly, a 25-year-old primigravida at 30 gestational weeks who had an isolated TGH with high blood pressure (BP) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…In countries struggling to manage gestational hypertension, such as South Africa, the association the authors found between anaemia and higher blood pressure may be especially important. Hypertensive disorders of pregnancy account for 18% of maternal deaths (Ngene & Daef 2021 ). In this study’s sample of pregnant women, 18%, 15% and 15% of women were prehypertensive at early, mid- and late pregnancy, respectively, despite routine iron, folic acid and calcium supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In countries struggling to manage gestational hypertension, such as South Africa, the association the authors found between anaemia and higher blood pressure may be especially important. Hypertensive disorders of pregnancy account for 18% of maternal deaths (Ngene & Daef 2021 ). In this study’s sample of pregnant women, 18%, 15% and 15% of women were prehypertensive at early, mid- and late pregnancy, respectively, despite routine iron, folic acid and calcium supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Placental histology may help elucidate features of placental-mediated diseases such as fetal growth restriction and preeclampsia. Placental vascular malformations (including maldevelopment and malperfusion) are among the microscopic features that may support the diagnosis of preeclampsia [ 25 ]. In the index case, the placenta was not sent for histology due to logistic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Гіпертензивні розлади вагітності, як-от гестаційна гіпертензія (ГГ) та прееклампсія, залишаються значною причиною материнської та плодової захворюваності і смертності в усьому світі [1][2][3][4][5][6]. Хоча точна патофізіологія цих розладів усе ще не до кінця зрозуміла, очевидно, що існують гемодинамічні шляхи, які відіграють вирішальну роль у їхньому розвитку [7][8][9].…”
Section: вступunclassified